DEVELOPMENT OF A METHOD TO REDUCE COMPUTATIONAL COSTS IN COMMUNICATION SYSTEMS WITH UFMC THROUGH THE USE OF NUMBER-THEORETIC TRANSFORMATIONS - M. I. Kalmykov; D. V. Yurdanov; I. A. Kalmykov; I. D. Efremenkov; E. A. Voloshin (Современная наука и инновации, 2022)
The search for new ways to improve the parameters of mobile radio communication systems OFDM led to the intensification of the development of mathematical models with the properties of finite algebraic structures. Proposed in this paper the transition to integer arithmetic for digital filtering, using number-theoretic transformations (NTT) can significantly reduce the computational cost in the formation of UFMC-signals, thereby reducing network latency.